Ileocolic Intussusception Secondary to Cecal Diverticulum Containing Heterotopic Gastric Mucosa in a 4 Month Old Boy: A Case Report - Manzoor, Hammad; Ahmad, Mushtaq; Rehman, Usama; Shah, Asif (Journal of Liaquat University of Medical & Health Sciences, 2025)
A case report of a 04-month-old boy is reported, who presented to the Pediatric Surgical Emergency Department of Sheikh Zayed Hospital, Rahim Yar Khan, with a history of abdominal distension, vomiting, reluctance to feed, and per rectal bleeding for two days. He was provisionally diagnosed as Intussusception with the typical symptoms' triad (i.e. abdominal pain, palpable mass and currant jelly stools). There was no associated history of fever, sore throat or constipation. On examination, he had abdominal distention, visible peristalsis, and a right upper quadrant palpable mass. Abdominal X-rays and ultrasonography supported the provisional diagnosis of Intussusception. Laparotomy findings showed an ileocolic intussusception secondary to the cecal diverticulum. Intussusception was manually reduced, followed by right limited hemicolectomy and ileocolic anastomosis, as some parts of the gut (intussusceptum) were not viable. Postoperatively, there were no active complaints, and the patient was made oral-free following the third postoperative day and was sent home on the 5th day following surgery. On the follow-up visit (10th post-op day), the infant was all right and playful, with no active complaints. The objective of this case report is to present a rare case of ileocolic Intussusception secondary to a cecal diverticulum containing heterotopic gastric mucosa in a 4-month-old boy, highlighting the clinical presentation, diagnostic challenges, surgical management, and the importance of recognizing uncommon etiologies in pediatric intussusception cases.